2010
DOI: 10.1186/1471-2377-10-111
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking and risk of Parkinson's disease: a case-control study in Japan

Abstract: BackgroundAlthough some epidemiologic studies found inverse associations between alcohol drinking and Parkinson's disease (PD), the majority of studies found no such significant associations. Additionally, there is only limited research into the possible interactions of alcohol intake with aldehyde dehydrogenase (ALDH) 2 activity with respect to PD risk. We examined the relationship between alcohol intake and PD among Japanese subjects using data from a case-control study.MethodsFrom 214 cases within 6 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…2 unmatched case‐control studies performed in China and Japan. 1 study did not find an association between total alcohol consumption and PD risk but found that sake consumption was associated with increased PD risk, another study found that frequent consumption of hard liquor was associated with decreased PD risk …”
Section: Analytical Epidemiologymentioning
confidence: 94%
See 2 more Smart Citations
“…2 unmatched case‐control studies performed in China and Japan. 1 study did not find an association between total alcohol consumption and PD risk but found that sake consumption was associated with increased PD risk, another study found that frequent consumption of hard liquor was associated with decreased PD risk …”
Section: Analytical Epidemiologymentioning
confidence: 94%
“…One case‐control study from Japan did not find a significant association between total alcohol consumption and PD risk . However, among the different types of alcohol, only Japanese sake (rice wine) was significantly associated with increased PD risk (adjusted or of ≥66 g ethanol per day; 3.39, 95% CI: 1.10–11.00) …”
Section: Analytical Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol intake might influence PD risk by the addictive behavior itself and the serum uric acid–elevating effect of beer, because serum uric acid is inversely associated with PD risk and could delay PD progression . However, results from the observational studies on alcohol intake and PD risk are not consistent, and both positive and negative results have been reported. In addition, the dose‐response relationship is still unclear.…”
mentioning
confidence: 99%
“…Several epidemiological studies have investigated the association between alcohol intake and the risk of Parkinson's disease (PD) . Results from some studies suggest a modestly lower PD risk with increasing alcohol intake whereas others did not find a protective effect . In addition, investigators of the NIH‐AARP Diet and Health Study reported that low beer consumption was associated with lower PD risk compared to nonbeer drinkers whereas greater liquor consumption was associated with a higher risk, suggesting that the effect of alcohol on PD risk may depend on specific types of alcoholic beverages …”
mentioning
confidence: 99%